Cerebrospinal fluid characteristics of patients treated with intrathecal nusinersen for spinal muscular atrophy. Issue 6 (19th October 2022) - Orbach, Rotem; Sagi, Liora; Sadot, Efraim; Tokatly Latzer, Itay; Shtamler, Anna; Zisberg, Tehila; Fattal‐Valevski, Aviva
Abstract: Introduction/Aims: There is limited information on the potential effects of repeated intrathecal antisense oligonucleotide drug delivery on cerebrospinal fluid (CSF) biochemical and blood cell profiles. This study aimed to examine longitudinal changes in the biochemical components (glucose, protein) and blood cell counts in the CSF of spinal muscular atrophy (SMA) patients treated with intrathecal nusinersen. Methods: We collected and analyzed clinical and CSF parameters (cell count, protein, glucose, culture) of 50 individuals with SMA during nusinersen treatment (22 type 1, 17 type 2, and 11 type 3). Results: The median protein concentration at baseline and during treatment was within the normal range but rose during treatment and was significantly above baseline at the time of the ninth intrathecal injection ( p  = 0.02, two‐tailed Wilcoxon matched‐pairs test, and p  = 0.0015, Friedman test for repeated measures). Further analysis showed that the increase in CSF protein concentration was evident for SMA types 2 and 3 patients, but not for type 1. This observation was also demonstrated by a significant correlation between the SMN2 gene copy number and the increase in CSF protein concentration (Spearman rank correlation test). Discussion: Our results demonstrate that a delayed increase in CSF protein concentration is expected during nusinersen treatment for SMA types 2 and 3. This might reflect the medication's effect and a possible therapeutic biochemical marker.